Lower gut microbiome diversity and higher abundance of proinflammatory genus Collinsella are associated with biopsy-proven nonalcoholic steatohepatitis. (3rd May 2020) - Astbury, Stuart; Atallah, Edmond; Vijay, Amrita; Aithal, Guruprasad P; Grove, Jane I; Valdes, Ana M
ABSTRACT: There is increasing evidence for the role of gut microbial composition in the pathogenesis of nonalcoholic fatty liver disease (NAFLD). Nonalcoholic steatohepatitis (NASH) is the most serious form of NAFLD where inflammation causes liver damage that can progress to cirrhosis. We have characterized the gut microbiome composition in UK patients with biopsy-proven NASH (n = 65) and compared it to that in healthy controls (n = 76). We report a 7% lower Shannon alpha diversity in NASH patients without cirrhosis (n = 40) compared to controls ( p = 2.7x 10 −4 ) and a 14% drop in NASH patients with cirrhosis (n = 25, p = 5.0x 10 −4 ). Beta diversity (Unweighted UniFrac distance) was also significantly reduced in both NASH ( p = 5.6x 10 −25 ) and NASH-cirrhosis ( p = 8.1x 10 −7 ) groups. The genus most strongly associated with NASH in this study was Collinsella (0.29% abundance in controls, 3.45% in NASH without cirrhosis (False Discovery Rate (FDR) p = .008), and 4.38% in NASH with cirrhosis (FDR p = .02)). This genus, which has been linked previously to obesity and atherosclerosis, was also positively correlated with fasting levels of triglycerides ( p = .01) and total cholesterol ( p = 1.2x 10 −4 ) and negatively correlated with high-density lipoprotein cholesterol ( p = 2.8x 10 −6 ) suggesting that some of the pathways present in this microbial genus may influence lipid metabolism in the host. In patients, we also found decreased abundance of some of the Ruminococcaceae which are known to produce high levels of short-chain fatty acids which can lower inflammation. This may thus contribute to pathology associated with NASH.